Financial Literacy and Digital Marketing Assistance Program for Rattan Handicraft MSMEs in Tempayung Village - Apriyasni Melati; Fifit S. Ni'mah; Ria Septiani (Edumedia Solution, 2026)
Rattan handicraft Micro, Small, and Medium Enterprises (MSMEs) in Tempayung Village, Kotawaringin Barat Regency, possess considerable potential to support local economic development. However, many business owners continue to face challenges in financial management and digital marketing, limiting business sustainability and market expansion. This community service program aimed to enhance the financial literacy and digital marketing capabilities of rattan handicraft MSMEs through an integrated approach involving training, hands-on practice, and mentoring. The program targeted all 10 identified rattan handicraft MSMEs in Tempayung Village. The implementation consisted of four stages: preliminary observation and needs assessment, preparation of training materials, financial literacy and digital marketing training, and mentoring followed by program evaluation. The results demonstrated that participants improved their understanding of simple bookkeeping, financial statement preparation, and the importance of separating personal and business finances. Furthermore, participants acquired practical skills in utilizing social media and online marketplaces as digital marketing platforms to promote their products. The integration of financial literacy and digital marketing proved effective in strengthening the managerial and marketing capacities of MSMEs, thereby supporting business competitiveness and sustainability. The program also demonstrated that collaboration among higher education institutions, local government, and MSMEs can effectively contribute to strengthening local economic development through community empowerment.